2020
DOI: 10.3389/fimmu.2020.00952
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Cell Motility: The Expanding Roles of Chemokines and Their Receptors in Malignancy

Abstract: The anti-tumor activities of some members of the chemokine family are often overcome by the functions of many chemokines that are strongly and causatively linked with increased tumor progression. Being key leukocyte attractants, chemokines promote the presence of inflammatory pro-tumor myeloid cells and immune-suppressive cells in tumors and metastases. In parallel, chemokines elevate additional pro-cancerous processes that depend on cell motility: endothelial cell migration (angiogenesis), recruitment of mese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 215 publications
(265 reference statements)
1
67
0
1
Order By: Relevance
“…Chemokines and their receptors not only drive the trafficking of leukocytes inside the tumor mass but also contribute to most aspects of tumor cell biology ( 1 ). High expression of CXCR4 is observed in hematological malignancies ( 57 59 ) and in many types of solid tumors, including melanomas and kidney, lung, brain, prostate, breast, pancreas and ovarian tumors ( 2 , 3 ), where it correlates with poor prognosis ( 59 ).…”
Section: Cxcr4/cxcl12 In Cancer Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemokines and their receptors not only drive the trafficking of leukocytes inside the tumor mass but also contribute to most aspects of tumor cell biology ( 1 ). High expression of CXCR4 is observed in hematological malignancies ( 57 59 ) and in many types of solid tumors, including melanomas and kidney, lung, brain, prostate, breast, pancreas and ovarian tumors ( 2 , 3 ), where it correlates with poor prognosis ( 59 ).…”
Section: Cxcr4/cxcl12 In Cancer Growthmentioning
confidence: 99%
“…They are also involved in tumor metastasis and invasion, and in the extension of neurites and axons of neurons (a part of a cell moves, while the cell body stays put). How chemokines and their receptors recruit hematopoietic cells to injured sites and tumors has been intensely investigated, whereas their involvement in the control of cell proliferation is less explored ( 1 ). Among chemokine receptors, CXCR4 is the most widely expressed, and is involved in numerous physiological and pathological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The activity of CXCR4 is mainly γ-mediated; however, CXCR7 is considered to be an atypical G protein-coupled receptor, as it does not cause intracellular Ca 2+ release when bound to a ligand ( 107 ). Some studies have shown that CXCR7 is a DcR that isolates extracellular CXCL12 or regulates the CXCR4 signaling pathway by forming a CXCR7-CXCR4 heterodimer ( 108 , 109 ). High expression of CXCR7 in human cancer types such as bladder cancer, glioma, colorectal cancer, ovarian cancer and breast cancer, and in tumor-associated blood vessels, may be critical for tumor cell survival, adhesion and growth ( 110 115 ).…”
Section: Role Of Inflammation Factors and Immune-related Cells In Thementioning
confidence: 99%
“…Although potential mechanisms capable of sculpting the cellular CXCL12 system such as ligand and receptor dimerization /oligomerization, receptor heteromerization, RGSs, and Grks emerged over recent years, the direct proof if and how these mechanisms dictate the molecular organization of the CXCL12 system in distinct cells still awaits experimental clarification. With the emerging role of ACKR3 and CXCR4 as therapeutic targets central to cancer, cardiovascular diseases, and inflammatory processes (Morein et al, 2020;Mousavi 2020;Wang et al, 2018b) knowledge of these sculpting mechanisms is becoming more and more eminent as they will allow for optimized therapeutic strategies. Finally, we hope that our present review will spark new interest into the function of ACKR3 which, as we feel, partially evaporated with its classification as an atypical chemokine receptor.…”
Section: Resultsmentioning
confidence: 99%